HISTORICAL DEVELOPMENT OF ADVERBS IN THE UZBEK LANGUAGE AND THE ISSUE OF THEIR LEARNING (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article presents the stages of historical development of ravishes in the Uzbek language, their specific characteristics. In addition, the article covers the problems of learning Uzbek language.